2021
DOI: 10.1016/j.commatsci.2020.110115
|View full text |Cite
|
Sign up to set email alerts
|

An atomistic investigation on the wear of diamond during atomic force microscope tip-based nanomachining of gallium arsenide

Abstract: This paper investigated the wear mechanism of diamond during the atomic force 2 microscope (AFM) tip-based nanomachining of Gallium Arsenide (GaAs) using molecular dynamics (MD) simulations. The elastic-plastic deformation at the apex of the diamond tip was observed during the simulations. Meanwhile, a transition of the diamond tip from its initial cubic diamond lattice structure sp 3 hybridization to graphite lattice structure sp 2 hybridization was revealed. Graphitization was, therefore, found to be the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Due to the unavailability of a single many-body potential function parameterized to describe all these atoms, a hybrid scheme was employed here using a hybrid/overlay scheme offered by LAMMPS. For the sake of brevity, the details of the potential function (which is readily available from the respective papers [12]) are not repeated here, but generally speaking, the covalently bonded interactions of C-C and the Ga-Ga, As-As and Ga-As interactions were all described by the analytical bond order potential developed by the research group of Albe et al [29][30]. As for the cross interactions between the atoms of the diamond tool and the Gallium Arsenide workpiece (Ga-C and As-C), a Ziegler-Biersack-Littmark (ZBL) potential function [31] (pair_style zbl in LAMMPS) was used which simply requires the atomic number and cut off parameters as an input.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unavailability of a single many-body potential function parameterized to describe all these atoms, a hybrid scheme was employed here using a hybrid/overlay scheme offered by LAMMPS. For the sake of brevity, the details of the potential function (which is readily available from the respective papers [12]) are not repeated here, but generally speaking, the covalently bonded interactions of C-C and the Ga-Ga, As-As and Ga-As interactions were all described by the analytical bond order potential developed by the research group of Albe et al [29][30]. As for the cross interactions between the atoms of the diamond tool and the Gallium Arsenide workpiece (Ga-C and As-C), a Ziegler-Biersack-Littmark (ZBL) potential function [31] (pair_style zbl in LAMMPS) was used which simply requires the atomic number and cut off parameters as an input.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…It is well known that the hardness and yield strength of a hard, brittle material decreases at higher temperatures [10] and the fracture toughness increases with the increase of temperature [11]. To this end, nanometric cutting of GaAs substrates at room temperature was recently investigated by the authors [12] and some conceptual fundamental aspects of room-temperature cutting of GaAs and the wear of diamond tool were discussed. In light of previous experience [13], the authors believe that hot machining conditions should improve the machinability of GaAs which became the key objective of this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A pyramid-shaped diamond tool was modeled to mimic the AFM tip, which contained nearly 17,132 atoms. The AFM tip was modeled as a rigid non-deformable body because the cutting distance considered in this work was too small, and the intention was not to study the tool wear, which is an aspect that was already reported previously [24]. The diamond tip was prescribed a velocity of 10 m/s into the GaAs workpiece, which was oriented on the (110) plane and cutting in the <001> direction, maintaining the z in the <-110> direction.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The two atomic layers near the boundary layer are thermostatic layers for the thermal equilibrium regulation of the system, and the model system is set to a Nose-Hoover. The remaining atoms obey the Newtonian layer of Newton's second law, which is used to respond to the mechanical properties of the material, i.e., the simulated system synthesis is an NVE ensemble [41][42][43].…”
Section: Simulation Modelmentioning
confidence: 99%